THE RELATIONSHIP BETWEEN EDUCATION AND EMPLOYMENT WITH PRE-MARRIAGE HEALTH CHECK COMPLIANCE ON PROSPECTIVE WOMEN - Umu Qonitun; Mariyatul Qiftiyah; Erna Eka Wijayanti; Dewi Tri Purwaningsih (Indonesian Midwifery and Health Sciences Journal, 2022)
Background : Bride and groom are a strategic target group in an effort to improve health before pregnancy. Premarital health examination is an effort to avoid maternal illness/death. Education and occupation are assessed to affect the compliance of premarital partners in premarital examination, pregnancy, childbirth and after delivery.The purpose of this study was to determine the relationship between education and work with compliance with premarital health examinations for prospective brides (CPW) at Plumpang Health Center, Tuban Regency. Method : analytical research. With the independent variable education and occupation and the dependent variable compliance who perform premarital health checks, using a cross sectional approach with a population of 50 CPW, sample 44 CPW. The sampling technique used random sampling and data collection using the Catin Visit Register measuring instrument and the Chi Square statistical test. Results: the research conducted at 50 CPW calculated the Pearson chi square statistical test, the results obtained a significance value of p = 0.003 so that it is smaller than the alpha value = 0.05 (p = 0.003 < = 0.05). Then H0 is rejected and Ha is accepted which means there is a relationship between Education, Employment and Compliance with Pre-Marriage Health Checks at the Plumpang Health Center, Tuban Regency. Conclusion : that there was a relationship between education, work and compliance with pre-marital health examinations at the Plumpang Health Center, Tuban Regency. keyword :  Education, employment, bride, premarital health